2018
DOI: 10.17512/jamcm.2018.3.03
|View full text |Cite
|
Sign up to set email alerts
|

The stability conditions of the cubic damping Van der Pol-Duffing oscillator using the HPM with the frequency-expansion technology

Abstract: In this paper, we perform the frequency-expansion formula for the nonlinear cubic damping van der Pol's equation, and the nonlinear frequency is derived. Stability conditions are performed, for the first time ever, by the nonlinear frequency technology and for the nonlinear oscillator. In terms of the van der Pol's coefficients the stability conditions have been performed. Further, the stability conditions are performed in the case of the complex damping coefficients. Moreover, the study has been extended to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…12. El-Dib 13 formulated a periodic solution for a strong time-delayed Duffing oscillator. In this investigation, a second-order analytic solution with a damping part was obtained using the multiple scales homotopy perturbation technique.…”
Section: Introductionmentioning
confidence: 99%
“…12. El-Dib 13 formulated a periodic solution for a strong time-delayed Duffing oscillator. In this investigation, a second-order analytic solution with a damping part was obtained using the multiple scales homotopy perturbation technique.…”
Section: Introductionmentioning
confidence: 99%
“…Satisfying conditions (66) should ensure that the roots of equation ( 64) are real. But this condition conflicts with the last condition in (65). So the frequency equation ( 64) is improper.…”
Section: Some Fallacies In the Study Of Non-conservative Issuesmentioning
confidence: 96%
“…Ex10: Consider the following generalized Van der Pol type oscillator 65 The homotopy equation isConsidering the frequency analysis so that we define the following frequency expansionAssuming that the function y(t;ρ) has been expanded asEmploying (151) and (152) with (150) and equating the identical powers of ρ to zero yieldSolution of the zero-order problem leads toSubstituting (155) into (154), the requirement of no secular term in y1(t) needsandSolution of (154) without secular terms becomesIf the first-order approximation is enough, then setting ρ1 in the expansions (151) and (152) yields the approximate solution and the frequency, respectivelyIt is observed that the above oscillation becomes in the form of the conservative behavior whenBy combining (159) and (161), we show the periodic solution can occur only when the amplitude A satisfies the following relationEx11: In the present example, we have develo...…”
Section: The Non-conservative Oscillators Through the Modified Homoto...mentioning
confidence: 99%
“…Through the examination of different design configurations and optimization methodologies made possible by this methodology, the field of MEMS is ultimately advanced, and the functionality and efficiency of MEMSs in a variety of applications are improved. Highly nonlinear problems have been solved using the homotopy perturbation method (HPM) [35][36][37][38][39][40]. This method provides the answer in the form of a series that quickly approaches the approximate answer.…”
Section: Introductionmentioning
confidence: 99%